Effects of a 6-week additional work on performance capacity: hints for a parasympathic overtraining? - Gasser, B. A.; Vogel, R.; Wehrlin, J. (Journal of Human Sport & Exercise, 2022)
Introduction: Maximum performance can only be achieved with an optimal balance of training and recovery. Already 15 years ago Jeukendrup & Hesselink (1994) mentioned that hints can be derived from lactate curves concerning a potential overreaching. In this small study we show the effects of a six-week standard infantry military training on performance capacity in young elite orienteers. The potentially induced overreaching and the ingoing alterations of heart rate patterns and lactate answers shall be analysed.